Oxygen isotope evidence for slab melting in modern and ancient subduction zones - Bindeman, IN; Eiler, JM; Yogodzinski, GM; Tatsumi, Y; Stern, CR; Grove, TL; Portnyagin, M; Hoernle, K; Leonid Danyushevsky (2005)
We measured oxygen isotope compositions of 34 adakites, high-Mg andesites, and lavas suspected to contain abundant slab and sediment melts from the Western and Central Aleutians, the Andes, Panama, Fiji, Kamchatka, Setouchi (Japan), and the Cascades. This suite covers much of the diversity of arc lavas previously hypothesized to contain abundant 'slab' melts. Measured and calculated values of δ 18O for olivine phenocrysts in these samples vary between 4.88‰ and 6.78‰ corresponding to calculated melt values of 6.36‰ to 8.17‰. Values of δ 18O for these samples are correlated with other geochemical parameters having petrogenetic significance, including Sr/Y, La/Yb, 87Sr/ 86Sr, and 143Nd/ 144Nd. Archetypical adakites from Adak Island (Central Aleutian) and Cook Island (Andean Austral zone), previously interpreted to be nearly pure melts of basaltic and gabbroic rocks in subducting slabs, have values of δ 18O slightly higher than those of normal mid-ocean-ridge basalts, and in oxygen isotope equilibrium with typical mantle peridotite (i.e., their subtle 18O enrichment reflects their Si-rich compositions and low liquidus temperatures, not 18O-rich sources). Other primitive adakites from Panama and Fiji show only subtle sub-per mil enrichments in the source. This finding appears to rule out the hypothesis that end-member adakites are unmodified partial melts of basaltic rocks and/or sediments in the top (upper 1-2 km) of the subducted slab, which typically have δ 18O values of ca. 9-20‰, and also appears to rule out them being partial melts of hydrothermally altered gabbros from the slab interior, which typically have δ 18O values of ca. 2-5‰. One explanation of this result is that adakites are mixtures of partial melts from several different parts of the slab, so that higher- and lower-δ 18O components average out to have no net difference from average mantle. Alternatively, adakites might be initially generated with more extreme δ 18O values, but undergo isotopic exchange with the mantle wedge ...